2011
DOI: 10.1007/s13313-011-0096-0
|View full text |Cite
|
Sign up to set email alerts
|

Organic inputs, tillage and rotation practices influence soil health and suppressiveness to soilborne pests and pathogens of ginger

Abstract: A field experiment was established in which an amendment of poultry manure and sawdust (200 t/ha) was incorporated into some plots but not others and then a permanent pasture or a sequence of biomass-producing crops was grown with and without tillage, with all biomass being returned to the soil. After 4 years, soil C levels were highest in amended plots, particularly those that had been cropped using minimum tillage, and lowest in nonamended and fallowed plots, regardless of how they had been tilled. When ging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…When litter is left on the soil surface, as in a no-till system, saprotrophic microbial communities become more structured due to the stratification of different nutrients through the soil (Holland and Coleman 1987). This heterogeneity of resources leads to increased microbial diversity found in no-till systems (Govaerts et al 2007) and could increase the ability of soils to suppress disease (Stirling et al 2012), but this has not been investigated specifically in a cover cropped perennial system.…”
Section: Plant Litter Affects Decomposer Communitymentioning
confidence: 99%
“…When litter is left on the soil surface, as in a no-till system, saprotrophic microbial communities become more structured due to the stratification of different nutrients through the soil (Holland and Coleman 1987). This heterogeneity of resources leads to increased microbial diversity found in no-till systems (Govaerts et al 2007) and could increase the ability of soils to suppress disease (Stirling et al 2012), but this has not been investigated specifically in a cover cropped perennial system.…”
Section: Plant Litter Affects Decomposer Communitymentioning
confidence: 99%
“…The principal component analysis (PCA) of the fungal community, as shown in Figure 3, also elucidated that significant variations occurred between the green garlic-and cucumber-planted soils among the individual samples during the whole experiment duration, as well as between the treatments with green garlic and cucumber mono-cropping. Agricultural soil management practices and cropping systems can directly affect the fungal community composition, as reported by numerous authors [49,[65][66][67][68]. Continuous cropping under a protected cultivation system is becoming an unrealistic approach, which considerably affects the biomass and activity of soil microorganisms unless the cropping pattern is modified [44,69,70].…”
Section: The Dynamics Of a Three-year Green Garlic/cucumber Crop Rotamentioning
confidence: 99%
“…Smith et al (2011) found greatest (74.2 t/ha) rhizome yield and minimal (7.0%) losses to pathogens in the pasture lay that had been cultivated prior to ginger planting. Stirling et al (2012) reported that organic inputs, tillage and rotation practices did not influence yellows disease. Results of bioassays were too inconsistent to draw firm conclusions, even soil management practices had little impact on disease severity.…”
Section: Management Cultural Practicesmentioning
confidence: 99%
“…Amendment of organic matter, including poultry manure and sawdust (200 t/ha) enriched diversity of soil microbial communities in these ginger fields (Rames et al, 2013). These practices also increased soil carbon levels and water infiltration rates which supported growth and yield of ginger and helped to suppress soft rot on ginger (Smith et al, 2011;Stirling et al, 2012). Neem seed cake was found most effective with least average mortality of 20.3 per cent followed by poultry manure (22.7 %) while evaluating organic and inorganic amendments to manage rhizome rot in pot culture studies (Kadam et al, 2014).…”
Section: Managementmentioning
confidence: 99%